The H-reflex study of the flexor carpi radialis muscle in healthy individuals - Mercan, Metin; Kuruoğlu, Reha (Frontiers in Neurology, 2024)
ObjectiveThis study aimed to investigate the physiological and anatomical factors influencing the flexor carpi radialis (FCR) H-reflex and to establish reference values for FCR H-reflex parameters in relation to these factors.MethodsThe FCR H-reflexes, elicited by median nerve stimulation, were assessed in 80 healthy individuals both at rest and during isometric voluntary contraction (IVC). Multiple linear regression analyses were performed with H-reflex parameters as the dependent variables, while age, gender, height, arm length, and weight were included as independent variables.ResultsThe FCR H-reflex was recorded bilaterally in nearly all healthy individuals (76 out of 80) during IVC, while it could be obtained in only 35% (28 out of 80) of these individuals at rest. During IVC, the maximum H-reflex amplitude (Hmax) and its ratio to the maximum M-response amplitude (Hmax/Mmax ratio) were significantly increased (p < 0.001). However, there were no changes in H-reflex latency, latency difference, conduction velocity (HRCV), or amplitude ratio (p > 0.05). In both conditions, age and arm length were the most important factors affecting H-reflex latency (p < 0.001), while HRCV was influenced only by age (p < 0.01). Women exhibited shorter H-reflex latencies (p < 0.01), and both Hmax amplitude and Hmax/Mmax ratio were higher in women during IVC (p < 0.05). The H-reflex amplitude ratio during IVC showed a tendency to decrease with age (p < 0.05).ConclusionThese findings suggest that FCR H-reflexes are more reliably elicited during IVC, and that both physiological and anatomical factors should be considered when assessing H-reflex abnormalities.